M1 macrophage subtypes activation and adipocyte dysfunction worsen during prolonged consumption of a fructose-rich diet - Gambaro, Sabrina Eliana (2018)
Fructose-rich diet (FRD) has been associated with obesity development, which is characterized by adipocytes hypertrophy and chronic low-grade inflammation. Interaction of adipocytes and immune cells plays a key role in adipose tissue (AT) alterations in obesity. We assessed the metabolic and immune impairments in AT in a murine obesity model induced by FRD at different periods. Adult Swiss mice were divided into groups of 6 and 10 weeks of fructose (FRD 6wk, FRD 10wk) or water intake (CTR 6wk, CTR 10wk). FRD induced increased in body weight, epidydimal AT mass, and plasmatic and liver Tg, and impaired insulin sensitivity. Also, hypertrophic adipocytes from FRD 6wk-10wk mice showed higher IL-6 when stimulated with LPS and leptin secretion. Several of these alterations worsened in FRD 10wk. Regarding AT inflammation, FRD mice have increased TNFα, IL-6 and IL1β, and decrease in IL-10 and CD206 mRNA levels. Using CD11b, LY6C, CD11c and CD206 as macrophages markers, we identified for first time in AT M1 (M1a: Ly6C+/−CD11c+CD206− and M1b: Ly6C+/−CD11c+CD206+) and M2 subtypes (Ly6C+/−CD11c−CD206+). M1a phenotype increased from 6 weeks onward, while Ly6C+/− M1b phenotype increased only after 10 weeks. Finally, co-culture of RAW264.7 (monocytes cell line) and CTR or FRD adipocytes showed that FRD 10wk adipocytes increased IL-6 expression in non- or LPS-stimulated monocytes. Our results showed that AT dysfunction got worse as the period of fructose consumption was longer. Inflammatory macrophage subtypes increased depending on the period of FRD intake, and hypertrophic adipocytes were able to create an environment that favored M1 phenotype in vitro.